Pendekatan Inovatif dalam Pengajaran Keterampilan Berbicara SD/MI - Shafa Qurratu A'yun; Maungi Dhotul Khasanah; Chusnul Chotimah; Musrikah Musrikah (Madrasah: Jurnal Pendidikan Madrasah, 2025)
Speaking skills are basic skills that are important to develop early on because they play a major role in the communication process, academic success, and social development of students. However, teaching speaking skills at the elementary school level is still less than optimal and tends to be monotonous. This article discusses innovative approaches in teaching speaking skills in elementary schools, such as aesthetic speaking, conversation, purposeful speaking, and drama activities. Through a literature review, it was found that the application of creative learning strategies can increase students' active participation, self-confidence, and verbal expression skills. Teachers act as facilitators in creating a fun, interactive, and communicative learning atmosphere. Innovation in teaching speaking skills is a strategic step in strengthening students' communication competencies as a whole.